The Corticosteroids in Paraquat PoisoningAre They the Sole Life-saving Drugs?: A Prospective Cohort Study - HA Krishnamurthy; S Bharathi; Vijay Sai Bhangari (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Paraquat poisoning has the highest mortality rate, as high as, 50%-90% due to multiorgan failure, inspite of early interventions by symptomatic medications in the best intensive care settings.The high degree of acute inflammation was found in the subjects of paraquat poisoning with multiorgan failure. There are no specific antidotes at present for the paraquat poison. Aim: To know the role of corticosteroid as a life-saving drug in paraquat poisoning. Materials and Methods: This prospective cohort study was conducted in the Department of Internal Medicine at KR Hospital, Mysuru, Karnataka, India. The duration of the study was eight months, from August 2022 to March 2023. A total of 108 subjects suffering from paraquat poisoning and were divided into two arms, arm one constitutes 70 (64.8%) subjects, they were given 1 gm of methylprednisolone, intravenously for five days with haemoperfusion. The arm two constitutes 38 (35.2%) subjects, they were treated with symptomatic drugs with haemoperfusion. Both the groups were followed-up during the hospital stay, to look for the outcome. The Chi-square test was applied to assess the association between two variables. The data was analysed using Statistical Package for Social Sciences (SPSS) version 25.0 (IBM Chicago). Results: The present study was done on 108 subjects, 43 (39.81%) were females and 65 (60.18%) were males. The majority of subjects showed high level of acute inflammatory mediators with multiorgan dysfunction. The subjects on corticosteroids (i.v. methylprednisolone) with haemoperfusion showed low mortality 12 (17.14%) and high survival rate 58 (82.85%) (p-value=0.001) as compared to the subjects on symptomatic treatment with haemoperfusion, with mortality of 36 (94.73%) (p-value=0.01). Conclusion: The early administration of high doses of corticosteroids in subjects with paraquat poisoning had been shown to provide tangible and measurable mortality benefits as compared to the symptomatic medications.